Machine learning, optimization, and big data : third International Conference, MOD 2017, Volterra, Italy, September 14-17, 2017, Revised selected papers /: third International Conference, MOD 2017, Volterra, Italy, September 14-17, 2017, Revised selected papers. (2018) - Unknown
No abstract available